Influence of nitrogen flux on structural and optical properties of InN films fabricated by PAMBE. (October 2017) - Wang, Hui; Zhao, Yang; Li, Xinzhong; Zhen, Zhiqiang; Li, Hehe; Wang, Jingge; Tang, Miaomiao
Highlights: InN epilayers were prepared by plasma-assisted MBE at different nitrogen fluxes. The nitrogen flux is critical to influence the physical properties of the InN layers. InN samples exhibited streaky cum spotty RHEED patterns at different N2 fluxes.